2011
DOI: 10.1111/j.1365-2885.2010.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of valnemulin in broiler chickens

Abstract: The objective of this study was to investigate the pharmacokinetics and bioavailability of valnemulin in broiler chickens after intravenous (i.v.), intramuscular (i.m.) and oral administrations of 10 mg/kg body weight (bw). Plasma samples were analyzed by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Pharmacokinetic characterization was performed by non-compartmental analysis using WinNonlin program. After intravenous administration, distribution was wide with the volume of dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…The corresponding MIC 99 and MPC levels were 0.10 and 2.40; 1.10 and 2.46 μg/mL, respectively[3336]. While the reported pharmacokinetic measurements of tilmicosin, tylvalosin and valnemulin after oral administration at the dose of 30, 20 and 10 mg/kg showed that concentrations of these agents were far more than the MPC determined in vitro [3739], revealing that the pharmacokinetic profile were above the MSW thoroughly. Consequently, it might be difficult for tilmicosin tylvalosin and valnemulin to select the resistance mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding MIC 99 and MPC levels were 0.10 and 2.40; 1.10 and 2.46 μg/mL, respectively[3336]. While the reported pharmacokinetic measurements of tilmicosin, tylvalosin and valnemulin after oral administration at the dose of 30, 20 and 10 mg/kg showed that concentrations of these agents were far more than the MPC determined in vitro [3739], revealing that the pharmacokinetic profile were above the MSW thoroughly. Consequently, it might be difficult for tilmicosin tylvalosin and valnemulin to select the resistance mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Valnemulin shows excellent effectiveness for treating mycoplasmal infection and rarely induces significant resistance (16). Its PK character is also favorable; however, its chemotherapeutic properties are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Serum was obtained by centrifuging blood samples at 3,000 rpm for 10 min and freezing at Ϫ20°C immediately until analysis (within 2 weeks). The valnemulin concentrations in serum were determined via a highperformance liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, as described previously (16)(17)(18). The limit of quantita- tion was confirmed to be 2.5 ng/ml (19).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the extensive use of valnemulin, several studies on the pharmacokinetics, pharmacodynamics, distribution, and metabolism (Yang et al ., ) have been conducted in various species, including rats (Yuan et al ., ), dogs (EMA, ), broiler chickens (Wang et al ., ; Zhao et al ., ,b), Muscovy ducks (Sun et al ., ), and swine (Huang et al ., ; Zhao et al ., ,b). These results showed that valnemulin possessed favorable profiles of well absorption, wide distribution, and rapid elimination.…”
Section: Introductionmentioning
confidence: 99%